PENGARUH PELATIHAN TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM CIPTA KARYA PROVINSI SUMATERA SELATAN - Amrillah Azrin (JURNAL KOMPETITIF, 2012)
Ã‚Â Ã‚Â Important part of the performance of employees staffing process. but there are very many organizations that ignore functions and employees work performance. Job training is insturument achieve organizational goals and hopes and aspirations of employees. that if there is no increase in training (X) then the performance (Y) fixed, and when carrying out the training is very significant effect on the performance of employees means that the training relationship with the employee's performance is very strong, , this means performance of the Office of the Public Works Department employees Settlements of South Sumatera Province affected by the presence of training conductedÃ‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â  Key words: Human Resources, Training, PerformanceÃ‚Â